PHOSPHORUS FERTILIZATION AND SOIL TEXTURE AFFECT POTATO YIELD - Lopes Martins, Jessyca Dellinhares [UNESP]; Soratto, Rogerio Peres [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Martins Dias, Pedro Henrique [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2018)
Potato (Solanum tuberosum L.) is a nutritionally demanding crop, and phosphorus (P) is a nutrient that exerts a large effect on tuber yield. However, as the availability of P is influenced by soil texture, there are doubts about how P supplementation affects the growth and yield of potato plants in different soil textures. Thus, here we aimed to evaluate the effect of P fertilization and soil texture on the nutrition, growth, tuber yield, and P use efficiency (PUE) of potato plants. The experiment was conducted under greenhouse conditions in a randomized block design with a 4x2 factorial scheme and five replications. The treatments were represented by four P rates (10, 50, 100, and 200 mg dm(-3) P) and two soil textures (clayey and sandy). The concentrations of P, Ca, and Mg in the leaves were higher in sandy soil, and P rates increased the concentrations of N, P, and Ca in the leaves of potato plants. Phosphorus fertilization increased plant growth, the amount of P accumulated in the shoot, and tuber yield in both soils; this trend was stronger in the potato cultivated in the clayey soil than in the sandy soil. The applied-PUE was not affected by soil texture. In the potato cultivated in the sandy soil, the taken up-PUE was reduced due to the decrease in dry matter production and an increase in P concentration in the organs of the plant with higher P fertilizer rates.
Keywords: Solanum tuberosum; Sandy soil; Clayey soil; Dry matter; Phosphorus accumulation